Effectiveness of Online Learning During the Covid-19 Pandemic in Indonesia - Fitriya Dwi Anggraini (STAI Miftahul Ula Nganjuk, 2022)
This study is based on the effectiveness of online learning during the covid-19 outbreak. The purpose of this study is to analyze the effectiveness of online learning systems in the future and provide the right solution for distance learning. The research method used is qualitatively descriptive. The study used two data sources: primary data and secondary data. Primary data is taken directly by conducting interviews with students with several universities. Secondary data is drawn from literature studies through books, articles, research journals and media. The result of this study is that the online learning system is the right policy in the current endemic period to reduce the number of spread of Covid-19 cases. The learning system still has obstacles in terms of supporting facilities and infrastructure and internet access available.